EKSTRAKURIKULER DHARMA GITA MEMBANGUN SIKAP SUPUTRA PADA SISWA - I Gusti Ayu Suasthi -; Komang Agus Triadi Kiswara -; Ida Ayu Putu Sari -; Ni Komang Ayu Restiti - (WIDYANATYA, 2023)
ABSTRACT Ethical education (morals) is very important as time goes by. With so many cases and phenomena indicating a decline in the moral and ethical qualities of the nation's children, schools are expected to be a place for internalizing the values ??of Hindu religious education in moral and moral teachings as the initial foundation for students to get along with their environment. As research material, researchers formulate several problems that will seek solutions, namely: 1) How is the process of internalizing the values ??of Hindu religious education through Dharmagita extracurriculars at SD No. 2 Kerobokan? 2) What are the factors that influence the process of internalizing the values ??of Hindu religious education through the Dharmagita extracurricular at SD No. 2 Kerobokan? 3) What are the Implications of Internalizing the Values ??of Hindu Religious Education through Dharmagita Extracurriculars for Suputra students at SD No. 2 Kerobokan? As a theoretical framework in describing the problems above, the researcher examines it with several theories, namely: cognitive theory, behavioristic theory, humanistic theory. In this study, researchers used a qualitative research design with a case study research design and data collection using observation, interviews and document recording methods. Based on the research that has been carried out, the following results are obtained: first, the process of internalizing the values ??of Hindu religious education through the Dharma Gita extracurricular at SD No. 2 Kerobokan, including: Extracurricular learning begins with initial activities, continues with core activities, and ends with activities end). Second, the factors that influence the process of internalizing the values ??of Hindu religious education through the Dharma Gita extracurricular at SD No. 2 Kerobokan: Internal factors (talent or innate, motivation), external factors (peers, the role of parents, cultural/multicultural diversity, social media). Third, the implications of internalizing the values ??of Hindu religious education through the Dharma Gita extracurricular for Suputra students at SD No. 2 Kerobokan: students become interested in learning the Dharma Gita, being polite, honest, cultured, ethical, moral, and with character. Keywords: Extracurricular, Dharma Gita, Suputra Students